The ANTENATAL multicentre study to predict postnatal renal outcome in fetuses with posterior urethral valves: objectives and design - Buffin-Meyer, Bénédicte; Wühl, Elke; Schaefer, Franz; Elsässer, Michael (Clinical kidney journal, 2020)
AbstractBackground. Posterior urethral valves (PUV) account for 17% of paediatric end-stage renal disease. A major issue in the management of PUV is prenatal pr